Development of a Web-Based Geographic Information System for Mapping and Monitoring the Spatial Distribution of Dengue Hemorrhagic Fever (DHF) Cases in Manado City - Christian Fendy Sumangkut; Mans L. Mananohas; Eric Alfonsius; Eliasta Ketaren (SEAN Institute, 2026)
Dengue Hemorrhagic Fever (DHF) remains a major public health concern in many regions of Indonesia, including Manado City. The spatial distribution of dengue cases is strongly influenced by environmental and geographical factors, highlighting the need for an information system capable of providing timely and accurate spatial data to support disease surveillance and control. This study aims to design and develop a web-based Geographic Information System (GIS) for mapping the spatial distribution of DHF cases in Manado City. The system was developed using the Waterfall software development model, which consists of the sequential phases of requirements analysis, system design, implementation, testing, and maintenance. The application was implemented using PHP as the programming language and MySQL as the database management system, while Leaflet.js and OpenStreetMap were utilized to provide interactive geospatial visualization based on GeoJSON data. The developed system enables users to visualize the spatial distribution of dengue cases through an interactive digital map, manage epidemiological data, and access statistical summaries via a web-based dashboard. Functional evaluation using Black Box Testing demonstrated that all major system functions operated correctly and fulfilled the specified requirements. The proposed GIS application provides an effective platform for spatial disease surveillance and supports evidence-based decision-making by public health authorities in planning and implementing dengue prevention and control strategies.